Presunivers Impact: Gen Z Siap Kerja – Unlock Your Future - Liswandi, Liswandi; Rianto Rahadi , Dedi (Lentera Ilmu Madani, 2025)
In the era of industrial disruption 4.0 and globalization, Generation Z faces real challengesin adapting their skills to the needs of the job market. The #kaburajadulu phenomenon thathas recently become a hot topic among young Indonesians reinforces this urgency, as itshows the tendency of the younger generation to pursue opportunities abroad due to thelack of readiness of the domestic system in preparing a competent and globally competitiveyoung workforce. To answer this challenge, the seminar “Presunivers Impact: Gen ZReady to Work – Unlock Your Future” was held as an effort to equip vocational high schoolstudents with the soft skills and hard skills needed in the world of work. This eventpresented professional speakers, including Ronaldsyah Fauzan Purba—a globalpractitioner in the field of procurement and strategic sourcing from Newmont Corporation,Australia—who shared cross-country experiences and successful strategies for facingcareer challenges globally. Through an interactive, practice-based training approach suchas interview simulations and industry case studies, this activity not only improves students’work readiness but also forms a more realistic and proactive long-term career perspective.